Percy Jackson & the Olympians: The Sea of Monsters BK 2 - Riordan, Rick (New York : Disney/Hyperion Books for Children, 2006)
Demi-god Percy Jackson and his friends must journey into the Sea of Monsters to save their camp. But first Percy will discover a secret that makes him wonder whether being claimed as Poseidon's son is an honor or a cruel joke.
Keywords: Mythology, Greek -- Juvenile fiction; Gods, Greek -- Juvenile fiction; Camps -- Juvenile fiction; Friendship -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Poseidon (Greek deity) -- Juvenile fiction; Mythology, Greek -- Fiction; Gods, Greek -- Fiction; Camps -- Fiction; Friendship -- Fiction; Fathers and sons -- Fiction; Poseidon (Greek deity) -- Fiction